Answer :

The given series is in the form of multiplication of two different APs.

So, the nth term of given series is equal to the multiplication of their nth term.

The First AP is given as follows: -

2, 4, 6…

where, first term(a) = 2

common difference(d) = 4 - 2 = 2

∴

n^{th} term = a + (n - 1)d

= 2 + (n - 1)2

= 2 + 2n - 2

= 2n

The Second AP is given as follows: -

4, 6, 8…

where, first term(a) = 4

common difference(d) = 6 - 4 = 2

∴

n^{th} term = a + (n - 1)d

= 4 + (n - 1)2

= 4 + 2n - 2

= 2n + 2

Now,

a_{n} = [n^{th} term of 2, 4, 6…] × [n^{th} term of 4, 6, 8…]

= (2n) × (2n + 2)

= 4n^{2} + 4n

Thus, the n^{th} term of series 2 × 4 + 4 × 6 + 6 × 8 + ... is

a_{n} = 4n^{2} + 4n

∴ a_{20} = 4 × (20)^{2} + 4 × 20 = 1600 + 80 = 1680

Hence, 20^{th} term of series is 1680.

Rate this question :

A person has 2 paRD Sharma - Mathematics

The sum of the seRD Sharma - Mathematics

How many terms ofRD Sharma - Mathematics

If <span lang="ENRD Sharma - Mathematics

Let a_{n}RD Sharma - Mathematics

Find the sum of 2RD Sharma - Mathematics

If <span lang="ENRS Aggarwal - Mathematics

Find the sum (41 RS Aggarwal - Mathematics

Find the sum (2 +RS Aggarwal - Mathematics

If<span lang="EN-RS Aggarwal - Mathematics